Die Theorie rationaler Erwartungen: Das Ende der Konjunkturpolitik? - Wilfried Fuhrmann (Kredit und Kapital, 1988)
Die Theorie rationaler Erwartungen: Das Ende der Konjunkturpolitik? Entgegen der allgemeinen Auffassung, daß aufgrund rationaler Erwartungsbildung eine Konjunkturpolitik obsolet geworden ist, zeigt dieser Survey, daß nicht einmal die Neue Klassische Makroökonomik (NKM) generell eine aggregative Outputwirkungslosigkeit einer vorhersehbaren Geld- und Fiskalpolitik anzeigt. Hierzu ist eine Vielzahl weiterer Annahmen erforderlich. Die Crux des Keynesianismus, der im monetären Bereich viele Gemeinsamkeiten mit der NKM aufweist, liegt in der lange Zeit dominierenden Hydraulik. Für eine kalendarische Zeit aussagefähige Analysen unter Berücksichtigung von Struktur- und Verteilungseffekten sowie der Charakteristika einer Geldwirtschaft sind erst noch zu erstellen. "The difficulty lies, not in the new ideas, but in escaping from the old ones, which ramify, for those brought up as most of us have been, into every corner of our minds" (J. M. Keynes, 1936, Preface, p.xxiii). Dieses ist heute auch, wie die Neue Klassische Makroökonomik zeigt, die Botschaft an keynesianische Mechaniker. – – Is the Rational Expectations Theory the End of Trade Cycle Policy? Contrary to widely announced views of politicians, and despite of the theory of rational expectations (not rational forming of expectations) this survey argues, that fiscal and monetary policies are powerful tools for stabilization-purposes. Of course, those times of a fine-tuning based on a fix-price IS-LM-framework (or other oversimplified models, velocity-concepts, etc.) preached by hydraulic-economists of all paradigms are gone – in economic-theory. But still we need departures away from atemporal (mainly neoclassical or walrasian) models as well as more insights into the structure of existing economic systems beyond Say; systems which are in general open to an uncertain future with regime-changes, structural shocks, etc. Examplified through the development within the "new classical macroeconomics" or the "new monetary economics", the message to keynesian mechanics is an old one: "The difficulty lies, not in the new ideas, but in escaping from the old ones, which ramify, for those brought up as most of use have been, into every corner of our minds" (J. M. Keynes, 1936, Preface, p. xxiii).
Keywords: 330